Adult form of Leigh's disease: a clinico pathological case with CT scan examination. Issue 11 (November 1984) - Gray, F; Louarn, F; Gherardi, R; Eizenbaum, J F; Marsault, C
Abstract : The clinical and pathological findings of a 31-year-old woman, in whom the diagnosis of Leigh's disease was made, are reported. CT scan examination with contrast enhancement showed symmetrical areas of low density, in both thalami, anterior limbs of internal capsules and corpus callosum. Longstanding chronic lesions involved the optic chiasma and the cerebral peduncles and consisted of myelin loss, status spongiosus, astrocytic gliosis and marked capillary proliferation. The neurons were spared. In the basal ganglia, internal capsules and corpus callosum, these lesions were more recent and consisted of focal necrosis, perivascular oedema and few lymphocytic perivascular cuffings.